(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Treacher Collins syndrome (TCS) or Franceschetti syndrome is an autosomal dominant disorder of craniofacial development with variable expressivity. It is named after Edward Treacher Collins (1862-1932), the English surgeon and ophthalmologist, who described the essential components of the condition in 1900. Incidence of this syndrome is approximately 1 in 50,000 live births and it affects both genders equally. The typical physical features include downward slanting eyes, micrognathia (a small lower jaw), Conducting hearing loss, under developed zygoma, drooping part of lateral lower eyelids, and malformed or absent ears. This article describes clinical and radiological features of TCS in a 07 yr old female child who had reported to the department of Dentistry and Radiology with the complaint of forwardly placed upper anterior teeth and hearing loss. Also pathogenesis, prenatal diagnosis, differential diagnosis, management and preventive aspects are discussed. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i2.21074